Field expansion of DNA polymerase chain reaction for early infant diagnosis of HIV-1: The Ethiopian experience - Peter Fonjungo; Mulu Girma; Zenebe Melaku; Teferi Mekonen; Amilcar Tanuri; Bereket Hailegiorgis; Belete Tegbaru; Yohannes Mengistu; Aytenew Ashenafi; Wubshet Mamo; Tesfay Abreha; Gudetta Tibesso; et al. (AOSIS, 2013)
Background: Early diagnosis of infants infected with HIV (EID) and early initiation of treatment significantly reduces the rate of disease progression and mortality. One of the challengesto identification of HIV-1-infected infants is availability and/or access to quality molecular laboratory facilities which perform molecular virologic assays suitable for accurate identificationof the HIV status of infants. Method: We conducted a joint site assessment and designed laboratories for the expansion of DNA polymerase chain reaction (PCR) testing based on dried blood spot (DBS) for EID insix regions of Ethiopia. Training of appropriate laboratory technologists and development of required documentation including standard operating procedures (SOPs) was carried out. The impact of the expansion of EID laboratories was assessed by the number of tests performed as well as the turn-around time. Results: DNA PCR for EID was introduced in 2008 in six regions. From April 2006 to April 2008, a total of 2848 infants had been tested centrally at the Ethiopian Health and Nutrition Research Institute (EHNRI) in Addis Ababa, and which was then the only laboratory with the capability to perform EID; 546 (19.2%) of the samples were positive. By November 2010, EHNRI and the six laboratories had tested an additional 16 985 HIV-exposed infants, of which 1915 (11.3%) were positive. The median turn-around time for test results was 14 days (range 14−21 days). Conclusion: Expansion of HIV DNA PCR testing facilities that can provide quality and reliable results is feasible in resource-limited settings. Regular supervision and monitoring for quality assurance of these laboratories is essential to maintain accuracy of testing.